Choice and quantity demand for improved and unimproved public water sources in rural areas: Evidence from Benin. (July 2019) - Gross, Elena; Elshiewy, Ossama
Abstract: Almost half of the world's population relies on public water sources for the daily drinking water supply. In this context, usage of improved public water sources is identified as a major contributor to good health. This research aims to identify important determinants of demand for water from improved and unimproved public water sources in rural areas. This is done by estimating choice and quantity models using a unique data set from a household survey conducted in rural areas of Benin, West Africa. The analysis identifies source and household characteristics that increase choice probability and water quantity demand for improved and unimproved public water sources. The price of water, the distance between the household and the water source, and the subjective quality of the source are relevant characteristics for the water source choice. Wealthy households and households with female heads have a higher probability to choose improved public water sources. After households have chosen a public water source, quantity demand is driven by wealth, household size and perceived taste. Price only affects water quantity demand from improved sources, while distance only affects water quantity demand from unimproved sources. Highlights: Choice and quantity demand estimation for public water sources in rural area. Price, distance, and subjective quality affect source choice probability. Wealth and female household heads increase choice probability for improved sources. Wealth, household size, and perceived taste affect water quantity demand. For quantity demand, price (distance) only relevant for improved (unimproved) sources.